Validating the use of the Wijma Delivery Expectancy/Experience Questionnaire in Mainland China: a descriptive, cross-sectional study - Lu Han; Jiaxin Wu; Hengchang Wu; Jun Liu; Yanqun Liu; Zhijie Zou; Juan Liu; Jinbing Bai (BMC, 2022)
Abstract Background Fear of childbirth (FOC) is a common psychological problem in Chinese pregnant women. FOC can influence both maternal health and infants' wellness. Special assessment tools for FOC in Mandarin Chinese are currently lacking. The aim of this study was to evaluate the psychometric properties of the Mandarin Chinese of the Wijma Delivery Expectancy/Experience Questionnaire Version A (W-DEQ-A). Methods We recruited 364 Chinese pregnant women from April 2021 to July 2021. Translation and cultural adaptation, as well as reliability and validity testing were conducted. Analyses included the content validity, structural validity, criterion-related validity, convergent validity and reliability. The content validity indices were used to assess the content validity of the tool. The structural validity was tested through exploratory factor analysis and confirmatory factor analysis. The Cronbach's alpha coefficient was used to evaluate the reliability of the W-DEQ-A Chinese version. Results The Chinese translation showed excellent similarities and equivalence to the original version, with the satisfactory content validity. Factor analysis indicated 5 factors, accounting for 57% of the total variance. Both criterion-related validity and convergent validity proved to be acceptable. The reliability was tested with a Cronbach's alpha coefficient of 0.911 for the total scale. Conclusion The W-DEQ-A Chinese version is a reliable and valid tool to identify FOC in Mandarin Chinese-speaking populations.